Problems faced by Independent Financial Advisers in the further enhancement of the market for Ethical Investments - Bahrdt, Katja Bahrdt (2009)
Ethical investment is a small but growing market, particularly for retail Ethical Investment products. Within this sector of the UK financial market, Independent Financial Advisers (IFAs) hold a key position placed as they are between consumers and suppliers, and have the potential to expand the market for Ethical Investment. It is suspected that several problems inside the market for Ethical Investment and the UK financial service sector are hindering the IFAs to do so. Hence, the purpose of this study was to discover the difficulties of Independent Financial Advisers (IFAs) to develop further growth of the Ethical Investment market in the UK. The specific concern was to look at the challenges, but also the opportunities Ethical Investments have to offer for IFAs.